CHAQ2020 - Snow Hill Island - Photographic and video data - CHAQ2020 - Snow Hill Island - Panoramas - Westin, Jonathan (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney.

After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903.

CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020.

This catalogue entry collects the photographic material, the panoramas, and the drone videos from Snow Hill Island.

The set consist of panoramas obtained from three scanning sessions with the Faro Focus m70 on January 12, 13 and 19, 2020 by Jonathan Westin. The original resolution of all but one is 20288 x 10144 pixels (one panorama has a resolution of 41434 x 20717 pixels). The outdoor panoramas were captured in early morning light on January 19 2020. Corresponding raw data point clouds in FLS-format for each of the scanning positions can be downloaded from the repository ”CHAQ2020 - Snow Hill Island - Spatial data”.

Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön.

Denna katalogpost samlar fotografier, panoraman, samt filmer inspelade med drönare, från Snow Hillön.

Se den engelska beskrivningen för mer information.

Panoramabilderna skapades under tre skanningsessioner med en Faro Focus m70 på den 12, 13 och 19 januari, 2020 av Jonathan Westin. Upplösningen på merparten av bilderna är 20288 x 10144 (ett av panoramorna har en upplösning på 41434 x 20717 pixlar). Utomhuspanoramorna fångades i tidigt morgonljus den nittonde januari 2020. Högupplösta punktmoln för varje panorama-position finns lagrade i katalogposten "CHAQ2020 - Snow Hillön - Spatiala data".
CHAQ2020 - Snow Hillön - Fotografiska data och videodata - CHAQ2020 - Snow Hillön - Panoraman
Keywords: Antarctica; Antarktis; Antarctic region; Swedish Antarctic Expedition, 1901-1904; Första svenska Antarktisexpeditionen, 1901-1904; Nordenskjöld, Otto, 1869-1928; Nordenskjöld, Otto, 1869-1928; History and Archaeology; Historia och arkeologi; Structure; Byggnader och byggnadsanläggningar